Executive Director's Message - Dow, Heather (Operating Room Nurses Association of Canada Journal, 2016)
Fast Forward! To quote Elizabeth Beck, the ORNAC Treasurer, “ORNAC is in fast-forward!” So… what has been happening, within ORNAC, during the past few months?